EFECTO DEL ESTADO DE DEGRADACIÓN EN LA RESPUESTA HIDROLÓGICA DE DOS UNIDADES DE ESCURRIMIENTO EN LA CUENCA DEL RÍO LA SIERRA, MÉXICO - Cesar Augusto Granada Isaza; Eusebio Ventura Ramos; Jurgen Baumann; Jose Luis Oropeza Mota; Nabil Mobayed Khodr (European Scientific Journal, ESJ, 2013)
﻿The hydrological response of a basin, watershed or runoff unit, is one of the main indicators of the balance between natural resources and their exploitation; an inadequate balance reduces the quantity and quality of natural resources. In this regard, it has been recognized the role of vegetation covered in the preservation of water resources and the transfer mechanisms between soil and vegetation. Usually, degradation starts as a result of human activities that disturb, destroy or decrease vegetation cover, subsequently leading soil degradation by the effect of different erosion agents. The aim of this study was to contribute to a better understanding of the interaction of precipitation, vegetation, soil and runoff in runoff units from a tropical basin in southern Mexico, hence, highlight the importance of vegetation as regulatory element in hydrological processes. According to the results, the hydrological response in tropical basins depends largely on factors such as the degradation state of the vegetation cover as well as variables related to the maximum and average intensity of precipitation. Even though, one should investigate further rainfall-runoff relationship in tropical areas; the results of this study allowed preliminary definition of variables such as peak flow, peak intensity, average intensity and total precipitation, should be considered for understanding rainfall-runoff relationship in different vegetation conditions, and their potential use in implementing best practices for water management and soil conservation.